Technology Integration in English Teaching: Reflections from Al Qolam In-Service Teachers - Syahrul Arifin; Joko Wibowo (LP3M KH Yazid Karimullah Institute, 2026)
Teachers were integrating technology into their English-language classrooms during their practice teaching as in-service teachers. A mixed-methods design, which included questionnaire administration, interviews, classroom observation, and document review for several different schools, was utilized for the study. Findings from this study indicate that integrating technology into the English-language classrooms improved student engagement, motivation, and interaction with their peers. The study also demonstrates that by providing the use of digital resources such as videos, audio files, and learning apps, teachers were creating interactive and engaging learning environments for their students. However, despite the positive outcomes from this study, the authors of the study identified numerous barriers that need to be addressed in order to successfully integrate technology into the English-language classroom. These barriers include limited access to devices, unreliable Internet service, lack of resources at schools, and insufficient training in the use of technology, which is usually part of university teacher education programmes. The evidence provided in this study demonstrates that university teacher education programmes and the challenges teachers encounter when teaching in the classroom are not in alignment. Despite having a positive attitude towards technology, the majority of the participants in this study believe that technology will continue to be an important component of English-language teaching.